FERMENTED MILK DRINKS WITH HERBAL EXTRACTS ON THE BASIS OF WHEY - Marina V. Kaledina; Anna N. Fedosova; Maria I. Shramko; Nadezhda P. Salatkova; Inna A. Martinova (Вестник Северо-Кавказского федерального университета, 2022)
Data of the application of researches of herbal extracts in reception of fermented milk drinks of a functional purpose are shown. Optimal technological parameters extraction process of biologically active substances from herbal were determined. Technology of production combined beverage was developed.